2022
DOI: 10.1098/rsbl.2021.0547
|View full text |Cite
|
Sign up to set email alerts
|

Humpback whales (Megaptera novaeangliae) attend both Mexico and Hawaii breeding grounds in the same winter: mixing in the northeast Pacific

Abstract: Humpback whales that assemble on winter breeding grounds in Mexico and Hawaii have been presumed to be, at least, seasonally isolated. Recently, these assemblies were declared Distinct Population Segments under the US Endangered Species Act. We report two humpback whales attending both breeding grounds in the same season—one moving from Hawaii to Mexico and the other from Mexico to Hawaii. The first was photo-identified in Maui, Hawaii on 23 February 2006 and again, after 53 days and 4545 km, on 17 April 2006 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…While automated matching algorithms have dramatically increased the amount of data available to delineate herds, they have also produced data that challenge our understanding of humpback movement and population structure. There have long been rare, documented cases of interchange of animals between feeding areas and between wintering areas in both the Northern Hemisphere (Calambokidis et al, 2001;Darling et al, 2022;Stevick et al, 2006Stevick et al, , 2016Urbán R. et al, 2000), and Southern Hemisphere (Félix et al, 2020;Garrigue et al, 2011;Steel et al, 2018;Stevick et al, 2013). However, the advent of large, integrated databases enabled by automated matching has resulted in an increase in the number of documented movements between wintering areas.…”
Section: Limitations and Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…While automated matching algorithms have dramatically increased the amount of data available to delineate herds, they have also produced data that challenge our understanding of humpback movement and population structure. There have long been rare, documented cases of interchange of animals between feeding areas and between wintering areas in both the Northern Hemisphere (Calambokidis et al, 2001;Darling et al, 2022;Stevick et al, 2006Stevick et al, , 2016Urbán R. et al, 2000), and Southern Hemisphere (Félix et al, 2020;Garrigue et al, 2011;Steel et al, 2018;Stevick et al, 2013). However, the advent of large, integrated databases enabled by automated matching has resulted in an increase in the number of documented movements between wintering areas.…”
Section: Limitations and Considerationsmentioning
confidence: 99%
“…Specifically, in the past decade humpback whale songs have been observed to be transmitted among wintering grounds within an ocean basin (Darling et al, 2019a;Garland et al, 2011). Darling et al (2019aDarling et al ( , 2022 concluded that these observations are indicative of ocean basin-wide panmixia, on the assumption that they could only result from extensive exchange of singing males between wintering areas. However, though singing was once thought to be largely confined to wintering grounds (Charif et al, 2001;Clapham & Mattila, 1990), we now know that humpback whales sing both on their feeding grounds late in the season and on migration (Clark & Clapham, 2004;Magnúsd ottir et al, 2014;Mattila et al, 1987;Noad & Cato, 2007;Norris et al, 1999;Schall et al, 2022;Stimpert et al, 2012;Tyarks et al, 2021;Vu et al, 2012), providing a mechanism for transmission of songs among winter areas in the absence of direct exchange of individuals between wintering grounds (Garland et al, 2013;Owen et al, 2019).…”
Section: Limitations and Considerationsmentioning
confidence: 99%
“…The humpback whales from Nayarit, Jalisco, and Colima coasts deserve special attention for management and conservation purposes. Humpback whales from three population units visit this region: (1) the Central America PU, occupying wintering areas off the Pacific coasts of Panama, Costa Rica, Nicaragua, Honduras, El Salvador, Guatemala, and south Mexico (Calambokidis et al, 2008;González-Peral 2011;Martínez-Loustalot et al, 2019Taylor et al, 2021); (2) the Offshore PU, distributed in the Revillagigedo Archipelago and the northwest coast of Mexico including the Baja California Peninsula, with their main feeding areas located in the Aleutian Islands and the north and the western Gulf of Alaska (Darling et al, 2022;González-Peral, 2011;Titova et al, 2017), and (3) the Coastal Mexico PU, distributed in the northern mainland Mexico and the Baja California Peninsula, with the main feeding areas on the US West Coast and British Columbia (Barlow et al, 2011;González-Peral, 2011;Martien et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The development of global networks of research collaborations and citizen science data collection of humpback whale fluke photos, as well as advancements in automated imaging techniques 17 have led to the discovery of numerous instances of humpback whales documented migrating outside of their expected ranges. These records include the detection of whales thousands of kilometers from their expected migratory location [18][19][20] , and include transoceanic movements between multiple breeding grounds 19,21 and between breeding and feeding grounds [22][23][24][25][26] ; the use of multiple distinct breeding grounds in the same season 26,27 ; migrations to areas beyond the known range of their stock 28 ; and feeding in known breeding grounds 29 .…”
mentioning
confidence: 99%